Development of a prenatal Maternal Self-report Inventory and verification of its reliability and validity - Nomachi, Shinobu; Emori, Yoko; Koizumi, Hitomi; Chishima, Yuta; Tronick, Edward (Universitas Andalas, 2024)
Â Purpose: This study aimed to develop a prenatal maternal self-report inventory (prenatal MSRI) based on the Maternal Self-Report Inventory (MSRI) and establish its reliability and validity. Methodology: The components of the prenatal MSRI were examined, and a 4-factor, 32-item questionnaire was developed and completed by 348 pregnant women. Findings: Exploratory factor analysis revealed 3 factors and 22 items in this scale. Cronbachâ€™s Î± coefficient for the total scale was .85. The testâ€“retest correlation coefficient for the total score was .86. The scale showed a significant positive correlation with the Rosenberg Self-Esteem Scale, indicating concurrent validity. Originality: The prenatal MSRI is a new instrument with confirmed reliability and validity. Practical Significance: This questionnaire, which takes approximately 5 minutes to complete, offers an instant assessment of maternal self-esteem. Practical and social implications: This scale can be used to assess maternal self-esteem specific to the gestational period, to identify the factors that may reduce self-esteem, and provide nursing support. Limitation: This scale has not been used on pregnant women who require hospitalization due to serious perinatal complications. Therefore, future research should apply this scale on all pregnant women.